Self-efficacy, self-regulation, and math anxiety as predictors of elementary students’ mathematical problem-solving - Arief Aulia Rahman; Nur ‘Afifah; Ahmad Rahmatika; Cesar Augusto Hernández Suárez (Universitas Hamzanwadi, 2025)
Mathematical problem-solving is a core competency in primary education, yet how self-efficacy, self-regulation, and mathematics anxiety jointly influence performance on tasks of varying cognitive demand remains unclear. This study assessed 180 fifth-grade students from five public elementary schools in Medan City, Indonesia, using three instruments: a 10-item Mathematics Achievement Test (6 LOTS and 4 HOTS items), a 20-item Self-Efficacy and Self-Regulation Scale (10 items per subscale), and the 9-item Modified Abbreviated Math Anxiety Scale (mAMAS). Multiple linear regression showed that self-efficacy (βLOTS = 0.279; βHOTS = 0.261) and self-regulation (βLOTS = 0.214; βHOTS = 0.223) significantly predicted performance on both lower- and higher-order thinking tasks (p < 0.001), explaining 63.7% and 55.2% of the variance, respectively. Mathematics anxiety was not a significant predictor (p > 0.23). Findings suggest that fostering students’ confidence and metacognitive strategies is more effective than reducing anxiety for improving mathematical problem-solving across cognitive complexity levels. Educational interventions should prioritize strengthening self-efficacy and self-regulation to support robust mathematical development in upper primary classrooms.